Kontribusi Sarjana dan Aktivis dalam Pembangunan serta Pemberdayaan Desa di Kabupaten Pamekasan Madura - Moh. Wardi; Munhari Munhari; Ismail Ismail; Ali Makki (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2019)
This study discusses the contribution of scholars and activists or former campus activists take an active role in building their respective regions. Since the Village Law was passed, many roles can be carried out in accelerating and equitable development between villages and cities. This research uses qualitative methods, namely research procedures that produce descriptive data in the form of written or oral words from people and observed behavior. The source of data in this study rests on human and non-human data sources. The research subject extra Campus activist students, HMI, PMII, GMNI, KAMMI and NGO in Pamekasan Regency. The results showed that Activist Strategy and Contribution to Build Villages in Pamekasan District served and returned to the village through the synergy of young people who had experience and insights on village development and welfare such as Karang Taruna, the establishment of BUMDes, the distribution of local tourism, the establishment of Small Micro Enterprises and Medium (UMKM), etc. The paradigm that needs to be built is actually activists creating opportunities and opportunities for employment, not looking for work.